The Role of Green Accounting in Enhancing Sustainability Practices in MSMEs in Semarang, Indonesia: Financial Performance Analysis Using the PLS-SEM Approach - Maulana Ihsan Yusufi Suyatno; Astohar Astohar; Mirna Dyah Praptitorini; Anisa Kusumawardani (Politeknik Ganesha Medan, 2026)
This study investigates the effect of adopting green accounting on sustainability performance and financial performance of micro, small, and medium enterprises (MSMEs) in Semarang, Indonesia. Data from 90 MSMEs across three categories—micro, small, and medium— were examined using structural equation modeling with partial least squares (PLS-SEM). The results show that adopting green accounting significantly improves sustainability performance (? = 0.76), indicating that implementing green accounting practices leads to better environmental, social, and economic outcomes. Additionally, sustainability performance positively affects financial performance (? = 0.27), demonstrating that sustainable practices lead to better profitability through cost efficiency, customer loyalty, and market access. While green accounting adoption also directly impacts financial performance (? = 0.39), the majority of its effect is mediated through sustainability performance. The bootstrapped mediation analysis confirms that sustainability performance fully discusses the connection between financial performance and the implementation of green accounting (Indirect effect = 0.21, p = 0.020). Additionally, 35% of the effect on financial performance is explained by sustainability practices. The study highlights that adopters of green accounting show significantly improved performance, particularly in medium-sized enterprises, where the t-value for sustainability performance was 7.33. These results contribute to the literature by demonstrating that green accounting not only supports environmental sustainability but also enhances financial performance. The results of the study are especially pertinent to policymakers and MSME practitioners in Semarang, providing insights into the importance of green accounting in improving business outcomes.